New Old South Church, ca. 1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of the New Old South Church, located at the northwest corner of Boylston and Dartmouth Streets. The facade of the church faces south-southeast towards Boylston Street, while the church's east elevation faces Dartmouth Street. The northeast corner of the Boston Public Library is visible along the left side of the photograph. Several electricity poles and street lamps line the intersection of Boylston and Dartmouth Streets. Other buildings located to the west and north of the New Old South Church are also included in the photograph. Designed by Cummings and Sears, 1874-75 8 3/4 x 7 5/16 Photographs